Analysis of the Digital Footprint of Orthopaedic Surgeons. (June 2021) - Subhash, Ajith K.; Sekimura, Troy; Kajikawa, Trent M.; Trikha, Rishi; Hsiue, Peter P.; Khoshbin, Amir; Photopoulos, Christos; Stavrakis, Alexandra
Abstract : Introduction: Patients increasingly rely on Google search to guide their choice of healthcare providers. Despite this trend, there is limited literature systematically characterizing the online presence of orthopaedic surgeons. The goal of this study was to identify the information patients see after queries of Google search when selecting orthopaedic surgeon providers. Methods: The Physician Comparable downloadable file from the Centers for Medicare and Medicaid Services was deduplicated and filtered. A list of orthopaedic surgeons within the United States was generated, of which a randomized sample was taken and queried using a Google Custom Search. The results for each surgeon's first page were classified into the following categories: (1) hospital-controlled content website, (2) third-party health website, (3) social media website, (4) primary academic journals, or (5) other. Results: The most frequently returned website was third-party health websites (43.3%). Statistically significant differences were observed in the categories across multiple comparisons, including academic and nonacademic orthopaedic surgeons, male and female providers, and surgeons from different graduation years. Discussion: Most of the results were attributed to third-party websites demonstrating that orthopaedic surgeons do not have notable control over their digital footprint. Increased patient visibility of physician-controlled websites and an objective rating system for patients remain potential areas of growth.